Inovasi Pelayanan Paket Perizinan Online Sebagai Upaya Peningkatan Kualitas Pelayanan Publik (Studi Pada BPPT Kabupaten Sidoarjo) - Oktavia, Betari Danu (Jurnal Administrasi Publik, 2015)
Abstract: The Innovation of Online Permit Package Service as The Effort to Improve Public Service Quality (Study of BPPT Kabupaten Sidoarjo). BPP in Sidoarjo Regency create an innovation service in the field of licensing that is Online Permit Package Service. An excess of this service compared to previous service is simple procedure, the requirements that simple, the speed of service and cost saving. There are factors supporting innovation in the development of innovation is that leadership, the culture of innovation, the quality of employees, the team work and partnership, the performance of innovation, as well as a network of innovation. There is little the obstacles in the implementation that is the attitude in the face of the risk and change, as well as aspects of administrative. But seen from the quality of the service provided by the presence of this innovation shown the result is a good enough. Evidenced by an absence of an increase in Community Satisfaction Index (IKM) after innovations Online Permit Package Service. Keywords: service innovation, service quality, online permit package service Abstrak: Inovasi Pelayanan Paket Perizinan Online sebagai Upaya Peningkatan Kualitas Pelayanan Publik (Studi pada BPPT Kabupaten Sidoarjo). BPPT Kabupaten Sidoarjo sebagai penyelenggara pelayanan perizinan menciptakan sebuah inovasi yaitu Pelayanan Paket Perizinan Online. Kelebihan layanan ini dibandingkan layanan sebelumnya yaitu prosedur yang sederhana, persyaratan yang sederhana, kecepatan pelayanan dan biaya yang hemat. Dalam pengembangan inovasi terdapat faktor pendukung yaitu kepemimpinan inovasi, budaya inovasi, kualitas pegawai, tim kerja dan kemitraan, kinerja inovasi, serta jaringan inovasi. Ada sedikit hambatan dalam pelaksanaannya yaitu sikap dalam menghadai resiko dan perubahan, serta aspek administratif. Namun dilihat dari kualitas pelayanan yang diberikan dengan adanya inovasi ini menunjukkan hasil yang cukup baik. Dibuktikan dengan adanya peningkatan Indeks Kepuasan Masyarakat (IKM) setelah adanya inovasi pelayanan paket perizinan online. Kata Kunci: Inovasi Pelayanan, Kualitas pelayanan, Pelayanan Paket Perizinan Online. Kata kunci: inovasi pelayanan, kualitas pelayanan, Pelayanan Paket Perizinan Online